2003
DOI: 10.1103/physreve.67.051702
|View full text |Cite
|
Sign up to set email alerts
|

Liquid crystal fibers of bent-core molecules

Abstract: Although the liquid-crystal research is well established in science, there are newly emerging exciting systems, that deserve extensive basic studies. One of these areas is the research of the bent-shaped molecules (so-called "banana liquid crystals"), which have delicate chirality and polarity properties. In this paper we show that these materials also have very unusual rheological features, such as the formation of stable fluid fibers and bridges. Under electric fields, these objects present striking mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
66
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 27 publications
5
66
2
Order By: Relevance
“…Among the more exotic of these are the B7 phases, in which the polarization field exhibits a periodic splay modulation, leading, in combination with the fluid smectic layering, to intricate textures in bulk samples (3)(4)(5)(6). As for many smectics appearing upon cooling directly from the isotropic phase via a first order transition, i.e., having no intervening nematic phase, the B7s are not easily aligned into macroscopically oriented domains of any sort with the anisotropic surface treatment methods such as optical-or mechanical-rubbed polymer surfaces or obliquely deposited silicon monoxide (SiOx) (7)(8)(9)(10)(11) that are typically useful for aligning LCs.…”
mentioning
confidence: 99%
“…Among the more exotic of these are the B7 phases, in which the polarization field exhibits a periodic splay modulation, leading, in combination with the fluid smectic layering, to intricate textures in bulk samples (3)(4)(5)(6). As for many smectics appearing upon cooling directly from the isotropic phase via a first order transition, i.e., having no intervening nematic phase, the B7s are not easily aligned into macroscopically oriented domains of any sort with the anisotropic surface treatment methods such as optical-or mechanical-rubbed polymer surfaces or obliquely deposited silicon monoxide (SiOx) (7)(8)(9)(10)(11) that are typically useful for aligning LCs.…”
mentioning
confidence: 99%
“…Freely suspended fluid filaments are among the most exotic structures formed by liquid crystalline materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Most of these unique structures are found in some mesophases of bent-core smectogens.…”
Section: Introductionmentioning
confidence: 99%
“…Such filaments represent either single cylindrical fibers or bundles of fibrils of about 2 µm diameter. The smectic layers are wrapped around the fibril axes [6,8]. The material can flow freely along the axis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the others, fibers made of liquid crystals [1][2][3] fall into the category of complex mediums and proved to be greatly attractive for multifarious applications [4,5] because these materials present the distinct characteristic of anisotropic nature in their physical properties [6,7]. Investigators have reported liquid crystal optical fibers (LCOFs) of different forms of constructions in respect of geometry as well as material distributions.…”
Section: Introductionmentioning
confidence: 99%